Hazardous area classification in petroleum and chemical plants : a guide to mitigating risk - Bahadori, Alireza (CRC Press, 2013)
"This book discusses fire hazards, occupancy hazards, extinguishing methods, and hazard identification and classification of materials. It provides simple, readily recognizable and easily understood markings for materials which will give at a glance, a general idea of the inherent hazards of any material, and the order of severity of these hazards as they relate to fire prevention, exposure, and control. Its objectives are to provide an appropriate alerting signal and on the spot information to safeguard the lives of both the public and emergency personnel."-- Provided by publisher
Keywords: Chemical processes -- Safety measures.; Chemical plants -- Management.; Petroleum refineries -- Safety measures.; elektronické knihy; electronic books